2007
DOI: 10.1042/bj20070519
|View full text |Cite
|
Sign up to set email alerts
|

The covalent modification and regulation of TLR8 in HEK-293 cells stimulated with imidazoquinoline agonists

Abstract: The mammalian TLRs (Toll-like receptors) mediate the rapid initial immune response to pathogens through recognition of pathogen-associated molecular patterns. The pathogen pattern to which TLR8 responds is ssRNA (single-stranded RNA) commonly associated with ssRNA viruses. TLR8 also responds to small, purine-like molecules including the imidazoquinoline IRMs (immune-response modifiers). The IRMs include molecules that selectively activate TLR7, selectively activate TLR8 or non-selectively activate both TLR7 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 60 publications
(83 reference statements)
1
16
0
Order By: Relevance
“…Human TLR8 has been shown to be tyrosine phosphorylated upon stimulation by an immunomodulator, 3M-003 (69). Mutational analyses revealed that among thirteen tyrosine residues in the cytoplasmic domain of TLR8, Tyr898, Tyr904 and Tyr1048 are critical for NF-κB activation.…”
Section: Tyrosine Phosphorylation Of Tlr8 and Tlr9mentioning
confidence: 99%
“…Human TLR8 has been shown to be tyrosine phosphorylated upon stimulation by an immunomodulator, 3M-003 (69). Mutational analyses revealed that among thirteen tyrosine residues in the cytoplasmic domain of TLR8, Tyr898, Tyr904 and Tyr1048 are critical for NF-κB activation.…”
Section: Tyrosine Phosphorylation Of Tlr8 and Tlr9mentioning
confidence: 99%
“…74 Similarly, TLR3 and TLR8 had phosphorylated tyrosine residues upon ligand engagement, which led to the recruitment of PI3K-p85 subunit. 75,76 However, these responses to TLR4 stimulation, including enhanced production of Tnf, Il6 and Ccl3 (also known as MIP1α). 29 Mechanistically, the authors found that signals provided by Akt1 were critical for induction of several miRNA species, including miRNA-155.…”
Section: Linking Tlr Signaling To Pi3k Activationmentioning
confidence: 99%
“…on May 9, 2018. by guest www.bloodjournal.org From Whether the major increase in TLR8 in antiubiquitin antibody immunoprecipitates reflects excessive ubiquitinylation of TLR8 or a TLR8 binding protein is not yet solved, but there is precedent for direct ubiquitinylation of TLR8 in response to the TLR7/8 agonist 3M-003. 41 However, the design of these previous studies involved overexpression of TLR8 in HEK-293 cells and detection of peptides by mass spectrometry. No ubiquitinylation sites or differential biologic function studies were reported by this group.…”
mentioning
confidence: 99%